Oil prices and renewable energy stock returns : time-varying relationship - Makkoeva, Anna (My University, 2014)
The study utilizes VAR and VEC models to investigate dynamic relationship between oil prices and stock prices of renewable energy companies. In order to exogenously control for the period of high oil price fluctuations, the data set is divided into two periods before and after the financial crisis of 2008 – 2009. Stock prices of technology companies and interest rates are considered as additional determinants contributing to the relationship. Results suggest that linkage among variables is time-varying. Prior to December, 2007 renewable energy stock prices are found to be positively impacted by alterations in technology stock prices and not affected by oil price changes. This indicates that investors considered renewable energy as more interrelated with the development of technology sector rather than the oil industry. After June, 2009, changes in renewable energy stock prices are not only explained by lagged changes in oil and technology stock prices, but also by “equilibrium error” in the previous period. A fraction of this error is corrected in the subsequent period, so that system partially adjusts towards equilibrium. The impact of oil prices on renewable energy stocks is positive showing that under the circumstances of persistently high oil prices and renewable energy market maturation, investors started incorporating oil price movements into their behavior.
Keywords: renewable energy stock prices; oil prices; VAR/VECM; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|